The Effect of Good Corporate Governance Implementation on the Decrease of Going Concern Audit Opinion Achievements in the Industry Sector of Consumption Goods Manufacturing 2017-2019 - Hania Novitawati (Perkumpulan Praktisi Akuntansi Indonesia, 2021)
The company is not only oriented towards profitability, but also in the survival of the company. Companies that have a strong relationship with financial statements that give rise to information asymmetry in line with agency theory. A third party, namely an auditor, is needed to review business continuity. Auditors provide reports in the form of opinions. A going concern opinion audit shows that the company is unable to maintain business continuity. This can be overcome by implementing good corporate governance. This study aims to examine the elements of good corporate governance that include audit ownership, managerial ownership, institutional ownership, independent commissioners, and audit committee on the acquisition of good governance audits. The method used is a quantitative approach, with descriptive analysis and logistic regression, because the dependent variable is a dummy variable, with a value ranging from 0 or 1. The data used is secondary data sourced from the related company's financial statements. The results of this study indicate that ownership, managerial ownership, institutional ownership, independent commissioners, and the audit committee have no significant effect on the acquisition of good governance audit opinion in the consumer goods industry sector listed on the IDX in 2017-2019.